The Importance of Water Clarity to Great Barrier Reef Tourists and Their Willingness to Pay to Improve it. (April 2016) - Farr, Marina; Stoeckl, Natalie; Esparon, Michelle; Larson, Silva; Jarvis, Diane
Using the Great Barrier Reef as a case study area, the authors investigate visitors' willingness to pay (WTP) to improve water clarity (WC). They also explore the extent to which people's objective and subjective measures of WC influence WTP. The results suggest that people's stated perceptions (importance and satisfaction) and the interaction between them have a significant influence on WTP. Those for whom WC was very important and who were very satisfied with WC were willing to pay more to preserve it. The importance variable interacts with subjective perceptions that drive behaviour. Thus one needs to consider not only satisfaction, but also the importance of the environment rather than using only subjective (or objective) measures when trying to explain behaviour. Further deterioration in WC could adversely affect the tourism industry and the average visitor would be willing to pay up to A14.5 per visit to help improve it (although this amount varies for different visitors).